The state of the world's refugees, 2000 : fifty years of humanitarian action - Cutts, Mark; Office of the United Nations High Commissioner for Refugees (Geneva : UNHCR ; New York : Oxford University Press, 2000)
"This book describes the development of international refugee law and the establishment of institutions devoted to the protection of refugees and other displaced people. It traces the major crises in which UNHCR has been involved since its establishment 50 years ago. Beginning with the mass displacement in Europe after the Second World War, the book addresses the flight of refugees from Hungary in 1956, crises associated with the process of decolonization in Africa, the Bangladesh refugee emergency in 1971, the sustained exodus from Indochina which began in the 1970s, and the large outflows resulting from the protracted wars of the 1980s in Afghanistan, the Horn of Africa, and Central America." "Looking at the challenges of the 1990s, the book examines the population shifts in the former Soviet region, the Kurdish exodus from northern Iraq following the Gulf war, the increasingly restrictive asylum policies in Europe and North America, and the recent crises in the Balkans, the Great Lakes region of Africa, East Timor, and the Caucasus." "In this timely and important publication, UNHCR emphasizes the need to find lasting solutions to problems of forced displacement. Without human security, it argues, there can be no peace and stability."--Jacket
-- The early years -- Decolonization in Africa -- Rupture in South Asia -- Flight from Indochina -- Proxy wars in Africa, Asia and Central America -- Repatriation and peacebuilding in the early 1990s -- Asylum in the industrialized world -- Displacement in the former Soviet region -- War and humanitarian action: Iraq and the Balkans -- The Rwandan genocide and its aftermath -- The changing dynamics of displacement
"Managing editor and principal author, Mark Cutts ... Main contributing authors, Joel Boutroue [and others]"--Page [iii]
Includes bibliographical references and index
Keywords: Refugees -- International cooperation -- History -- 20th century; Humanitarian assistance -- History -- 20th century; Refugees -- Legal status, laws, etc. -- History -- 20th century; Office of the United Nations High Commissioner for Refugees -- History -- 20th century